PTU-002 The hepatic inflammatory milieu of acetaminophen induced acute liver falure induces alternatively activated, M2-like, macrophages. (28th May 2012) - Antoniades, C G; Zingarelli, V; Possamai, L; Khamri, W; Vergis, N; Mitry, R; Quaglia, A; Bernal, W; Auzinger, G; Ma, Y; Wendon, J; Thursz, M
Abstract : Introduction: Human acetaminophen-induced acute liver injury (AALF) is characterised by areas of hepatic necrosis that are infiltrated by macrophages (mϕ) and elevated concentrations of anti-inflammatory cytokines. Anti-inflammatory mediators, such as secretory leucoprotease inhibitor (SLPI) and IL-10 contribute to the functional switching of mϕ from a proinflammatory (M1) type to an alternatively activated (M2) phenotype that promotes tissue repair processes. We sought to determine the effects of the hepatic inflammatory milieu on peripheral monocytes (MO) and MO derived mϕ in AALF. Methods: Phosphoflow technique was used to evaluate NF-kBp65, STAT-3 signalling pathways in ex-vivo MO in 10 AALF patients and 10 healthy controls (HC). Results expressed as MFI and ratio of activation. Regional changes (portal vein [PV]), hepatic vein [HV])) were assessed in 5 AALF patients at time of transplantation. Serum (AALF [n=34]; HC [n=15]), hepatic (AALF [n=7]; HC [n=8]) and regional levels of TNF-α, IL-10 and SLPI were measured. The effect of the hepatic microenvironment was assessed in five cell culture experiments: purified CD14+ MO from HC were incubated with homogenates from AALF and culture medium (CM). Results: In MO, TLR-4 stimulation reduced NF-kBp65 expression in AALF compared to HC (0.8 vs 1.6; p=0.001). Ex-vivo STAT-3 expression was significantly elevated in AALF patients compared to HC (600 vs 232; p=0.02). AALF patients had higher serum concentrations of IL-10 (170 vs 40; p<0.02), SLPI (71200 vs 43310; p<0.0001) compared to HC. A trans-hepatic (HV>PV) gradient was seen for IL-10 and SLPI but not for TNF-α. Hepatic levels of IL-10 (2 vs 0.6; p<0.02) and SLPI (442 vs 116; p<0.01) were significantly elevated in AALF compared to HC tissue, with peak concentrations of IL-10 detected in necrotic areas while SPLI was highest in areas of hepatic regeneration. In vitro exposure to AALF milieu induced a unique CD14+CD16+ macrophage phenotype characterised increased expression of alternative (M2) activation markers- CD36 (78 vs 55%; p=0.01) and CD163 (58 vs 32.5%; p=0.04), reduced LPS-induced TNF-a (19.8 vs 40.5%; p=0.02), IL-6 (13.2 vs 22%; p=0.04) and enhanced phagocytosis (80.5 vs 70%; p=0.03) when compared to MO incubated CM. Conclusion: In AALF, circulating monocytes show modulations in intracellular signalling pathways compatible with anti-inflammatory responses. Our data also indicate that the anti-inflammatory hepatic microenvironment preferentially induces alternatively activated (M2)-like macrophages that may be implicated in resolution of acute liver injury. Competing interests: None declared.